Efektivitas Kelas Parenting dalam Meningkatkan pola Asuh Anak di Kelurahan Banyu Urip - Dayat, Dayat; Kalvin Edo Wahyudi (IAI Nasional Laa Roiba Bogor, 2024)
The effectiveness of the Parenting Class in improving parenting in Kelurahan Banyu Urip shows positive and significant results. The program facilitates learning good parenting practices and actively involves parents in efforts to prevent child abuse and neglect. In addition, the program builds solidarity networks among parents and provides emotional support. The results show that the program has successfully changed parenting patterns and increased the role of parents in child development. Suggestions for improving the program include conducting ongoing evaluations and replicating similar programs in other areas to reach more families who can benefit.